2019
DOI: 10.1002/star.201900150
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an Extrusion Cooking Process to Increase Formation of Resistant Starch from Corn Starch with Addition of Citric Acid

Abstract: Effects of extrusion cooking process (ECP) with citric acid (CA) addition on the physicochemical changes and resistant starch (RS) formation in native corn starch (NCS) are evaluated. NCS at different feed moisture levels (18–32%) and CA concentrations (0–10.3%), are subject ECP under constant conditions of screw speed (233 rpm) and die temperature (127 °C). The obtained extrudates are stored at 4 °C for 120 h and then at room temperature. The water absorption index (WAI), water solubility index (WSI), RS cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
5
0
5
Order By: Relevance
“…The higher the temperature, the larger the extent of changes and starch transit from a crystalline to a fully amorphous state, which results in increased digestibility [ 10 ]. To obtain a higher content of resistant starch in extruded snacks, chemically modified starch (RS type 4) may be added before or during extrusion [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The higher the temperature, the larger the extent of changes and starch transit from a crystalline to a fully amorphous state, which results in increased digestibility [ 10 ]. To obtain a higher content of resistant starch in extruded snacks, chemically modified starch (RS type 4) may be added before or during extrusion [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…WSI can be understood as an indicator of starch degradation during processing, in which low values indicated that starch was not wholly hydrolyzed, containing few soluble molecules. [ 22 ] Therefore, starches gelatinized at 1:5 (S:W) using 100 °C presented a higher amount of soluble solids, hinting at more significant starch damage during the processing. Previously, Sigala‐Adame [ 21 ] observed this behavior to increase WAI and reduce WSI in potato starch treated with ohmic heating.…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity was significantly affected ( p < .05) by toasting temperature and time; decreasing over the toasting time, with a higher loss at 260°C (Figure 2a). This indicates that at higher temperature and toasting time greater starch dextrinization is caused (Rolandelli et al, 2021), inducing to higher rupture of starch structure, which decreases the viscosity (Neder‐Suárez et al, 2020). The latter can be observed in the micrographs of toasted blue maize, where a disruption of the starch granules and loss of their distribution and spherical form is shown with a greater effect at 260°C (Figure 2d), compared to unprocessed maize (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%